3
$\begingroup$

We'll consider $(N, g)$ a Riamannian Manifold and $\overline{g} = e^{2f}g$ a conformal metric. Let M be a hypersurface in N, $\overline{H}_M$ and $H_M$ the mean curvature of M with respect to the metrics $\overline{g}$ and g, respectively. I would like some help to prove that

$$ \overline{H}_M = e^{-f}( H_M -2g( \nabla f, \eta)) $$

where $\nabla$ is the gradient with respect to metric g and $\eta$ is a normal vector field in M.

$\endgroup$
1
  • 4
    $\begingroup$ Your formula seems to be slightly off in a few ways. For example, do you really want $\eta$ to be a tangent vector field to $M$ rather than the normal vector field? $\endgroup$ Jan 27 at 22:24
3
$\begingroup$

Let me use the transformation $\overline g = e^{2f}g$ to simplify some notations (and I guess your formula also use this convention). Near a point $p\in N,$ let $\{e_i\}$ be an orthonormal frame with respect to $g,$ and $\eta$ be a normal. Then with respect to $\overline g,$ we have $\overline e_i = e^{-f}e_i$ form an orthonormal frame near $p$ and $\overline\eta=e^{-f}\eta$ being the normal. Then \begin{align} \overline h_{ij} & = \langle\overline\nabla_{\overline e_i}\overline e_j,\overline\eta \rangle_{\overline g}\\ & = e^{2f}\langle e^{-2f}\overline\nabla_{e_i}e_j, e^{-f}\eta\rangle_g\\ & = e^{-f}\langle \nabla_{e_i}e_j-\delta_{ij}\nabla f,\eta \rangle_g\\ & = e^{-f}( h_{ij} -\langle \nabla f,\eta\rangle_g\delta_{ij})\\ \end{align} where we use the transformation of the Levi-Civita connection, i.e., $$\overline\nabla_X Y = \nabla_XY + (Xf)Y + (Yf)X - \langle X,Y\rangle_g\nabla f.$$ Thus \begin{align} \overline H & = \sum_{i=1}^{n-1}\overline h_{ii}\\ & = \sum_{i=1}^{n-1}e^{-f}(h_{ii} - \langle \nabla f,\eta\rangle_g)\\ & = e^{-f} (H-(n-1) \langle \nabla f,\eta\rangle_g), \end{align} where $n$ is the dimension of $N,$ so in your case $n-1=2.$

$\endgroup$
10
  • 3
    $\begingroup$ A couple of comments to get a correct formula: First, if $\bar g = \mathrm{e}^{2f} g$ and $\mathbf{e}_i$ is a $g$-orthonormal frame near $p$, then $\mathrm{e}^{-f} \mathbf{e}_i$ is a $\bar g$-orthonormal frame. (Note the minus sign.) Second, the mean curvature is the average of the principal curvatures, not the sum, so you are missing a normalization factor. For example, check your formula for the unit sphere $M=S^{n-1}\subset\mathbb{E}^n$ with $g = |dx|^2$, $\mathrm{e}^{2f} = |x|^{-2}$, and $\eta$ the outward normal. You should get $H=-1$ and $\bar H = 0$. $\endgroup$ Jan 31 at 11:25
  • $\begingroup$ @Robert Bryant Hello Robert. Thanks for your comment! Just one question. If $\overline g = e^{2f}g$ and $\overline e=e^{-f}e,$ isn't it correct that $\langle \overline e,\overline e\rangle_{\overline g} = e^{-2f}\langle e^{-f} e, e^{-f} e\rangle_{g} = e^{-4f}|e|^2_g?$ $\endgroup$
    – User
    Jan 31 at 11:37
  • 1
    $\begingroup$ No, that is not correct. $g$ is a a tensor of type $(0,2)$ while vector fields are tensors of type $(1,0)$. Maybe you are confused by the notation $\langle X,Y \rangle_g$, which means $g(X,Y)$, so $\bar g(X,Y) = e^{2f} g(X,Y) = g(e^fX,e^fY)$. In particular, if $g(X,X)=1$, then $\bar g(e^{-f}X,e^{-f}X) = 1$. $\endgroup$ Jan 31 at 11:52
  • $\begingroup$ @RobertBryant So when people write $\overline g = e^{2f} g,$ it doesn't mean that locally $\overline g_{ij} = e^{2f}g_{ij}$ (which implies $\overline g^{ij} = e^{2f}g^{ij}$), is it? $\endgroup$
    – User
    Jan 31 at 12:00
  • 1
    $\begingroup$ Yes, $\bar g = e^{2f} g$ means what you say, and also $\bar g^{ij} = -e^{2f} g^{ij}$, but that's not relevant. The point is that a vector field in local coordinates is $X = X^i\,\partial_i$, with $ |X|_g^2 = g_{ij}X^iX^j$. $\endgroup$ Jan 31 at 14:03

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.